If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8y-11=6(y-5)+2
We move all terms to the left:
8y-11-(6(y-5)+2)=0
We calculate terms in parentheses: -(6(y-5)+2), so:We get rid of parentheses
6(y-5)+2
We multiply parentheses
6y-30+2
We add all the numbers together, and all the variables
6y-28
Back to the equation:
-(6y-28)
8y-6y+28-11=0
We add all the numbers together, and all the variables
2y+17=0
We move all terms containing y to the left, all other terms to the right
2y=-17
y=-17/2
y=-8+1/2
| 2n2+9n+10=0 | | 3x+15=10+× | | 9(x+2)+6=9x+5 | | 5x-17=13x-10 | | 5p-6=31 | | 4.6=-v/8+3.7 | | 0.8x+2.4=0.7x+1.1 | | (10x-22)+(3x+20)=180 | | -1.6c=3.2 | | 5n^2-24n+21=5 | | x/7-20=15 | | 5k-1/5=3 | | 10x+2=3(3x+8) | | 1.5x=68 | | 12=8+x/4 | | 2x+3(-2x+5)=31 | | 9x-5x+3=x-6+9 | | 2.5x+7=42 | | 8p+10=26 | | y-3=^1 | | 3y+32=23+7y | | 6k-(2+k)=-(2k+2) | | 7y+10=4y-2 | | 7n-150+n=20n-80-40n | | 12m-4=12+3+4m | | 7-3/x=4 | | j-6=(1)/(2)j+3 | | 9(4+v)+38v=15v | | x+(70-x)=70 | | 18=3-(z+8) | | 20+20=4•w | | 4a^2+a-5=0 |